THE URGENCY OF THE ROLE OF ORGANIZATIONAL MOTIVATION IN MANAGING PRIVATE ISLAMIC EDUCATION INSTITUTIONS IN ERA 4.0 - Dodo Suhada, Dodo Suhada; Hisam Ahyani; Syamsudin; Sartono (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2021)
The importance of the Role of Organizational Motivation in Managing Private Islamic Educational Institutions, especially in Era 4.0 is a necessity, where many private Islamic higher education institutions are now established to compete with each other, where the 4.0 era (disruption) which is now present in the midst of Society 5.0 needs a strategy specifically to maintain the existence in every private Islamic higher education institution. The purpose of this study is to find out the implementation of organizational motivation by managers of private Islamic universities in managing private Islamic educational institutions in Era 4.0 so that they can still exist and be able to compete; To find out what obstacles are faced by managers of private Islamic universities in maintaining the existence of their institutions in Era 4.0; and to find out the solutions offered to overcome these obstacles. The method used in this research is library research, with data sources obtained from various literature books, journals, internet related to the Urgency of the Role of Organizational Motivation by managers of private Islamic universities in Indonesia in Managing their Institutions in Era 4.0. The results show that the success of a manager of a private Islamic higher education institution is the ability of higher education managers to manage the institutions they lead, one of which is through the role of motivation for the human resources they manage and using a unique and attractive management model in order to improve the performance of human resources, facilities, facilities and adequate infrastructure to be able to compete with other private Islamic higher education institutions in Indonesia.